(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
An important part of forensic analysis in cases of sexual assault is the screening of clothes and bedding items for seminal fluids. Sometimes, without knowing the importance of these evidences, the victims do the laundry or wash the clothes after sexual abuse before the police have a chance to seize them for forensic investigation. Most of the time, washed clothes are not tested either because of time delays or for the reason that any detectable DNA will not result after washing. The purpose of this study was to test whether viable amounts of DNA could be obtained from laundered semen stained clothing, despite multiple washings. In the present work, samples were collected from volunteer donors. Cotton gauze was stained with semen and after several washes from tap water and detergent; preliminary screening of seminal stain is done using the Acid Phosphatase (AP) test. DNA was extracted using the phenol - chloroform method and quantified using RT PCR. The sensitivity and stability of the AP test decreased after each successive wash and the number of spermatozoa was found to be less than half after each successive wash. The findings of this study suggest that evidence retrieval should be included in the investigation, even though clothes have been washed multiple times in sexual offenses.